Is Nonoperative Management Warranted in Ventral Hernia Patients With Comorbidities?: A Case-matched, Prospective, Patient-centered Study. Issue 4 (October 2016) - Holihan, Julie L.; Henchcliffe, Blake E.; Mo, Jiandi; Flores-Gonzalez, Juan R.; Ko, Tien C.; Kao, Lillian S.; Liang, Mike K.
Abstract : Objective: The aim of this study was to determine patient-centered outcomes of nonoperative treatment of a ventral hernia. Summary of Background Data: Nonoperative management of ventral hernias (VHs) is often recommended for patients at increased risk of complications; however, the impact of this management strategy on outcome and quality of life (QoL) is unknown. We hypothesize that QoL and function are better among patients with VHs managed operatively. Methods: Patients with a VH from a single-center hernia clinic were prospectively enrolled between June 2014 and June 2015. Nonoperative management was recommended if smoking, obesity, or poorly controlled diabetes was present. Primary outcomes were patient-centered outcomes, including QoL and function, which were measured using a validated, hernia-specific survey (modified Activities Assessment Scale) before surgeon' consultation and at 6 months. Other outcomes included surgical site infection (SSI) and recurrence. Risk-adjusted outcomes between nonoperative and operative groups were compared using: paired t test on a propensity score-matched subset and multivariable analysis on the overall cohort. Results: A total of 152 patients (nonoperative = 97, operative = 55) were enrolled. In the propensity-matched cohort (n = 90), both groups had similar baseline QoL and function scores, but only repaired patients had improved scores on 6-month follow-up. In the overall cohort, nonoperative management was strongly associated with lower function scores (log odds ratio = −26.5; 95% confidence interval = −35.0 to −18.0). Conclusions: This is the first prospective study comparing management strategies in VH patients with comorbidities. Elective repair improves hernia-related QoL and function in low- to moderate-risk patients and should be considered in appropriately selected patients. Abstract : Supplemental Digital Content is available in the text